Fighting with depression. Offensive actions of the Red Army for Zulawy Wislane in 1945 - Gliniecki, Tomasz (Armia kontra natura, 2020)
The Soviet offensive at the end of March 1945 included part of Zulawy – the port complex of Gdansk and Gdynia was conquered, but then the defenders blew up the flood control system and flooded some of the depression areas, preventing the Red Army from attacking from the West. The last defenders from Gdansk withdrew in the water-cut region. After a few days of fighting in April, a large part of the General I. Fiediuninski’s 2nd Shock Army was moved to other areas, and Wehrmacht troops remained in the estuary of the Vistula river and at the base of the Vistula Spit until the last day of the war in Europe.